Displaced persons in Queensland: Stuart migrant camp - Persian, Jayne (Queensland Review, 2018)
This article examines the lived experience and recent commemorative efforts relating to the experience of displaced prsons who were sent to Queensland in the post-war period. 170,000 displaced persons — predominantly Central and Eastern Europeans — arrived in Australia between 1947 and 1952. They were sent to reception and training centres upon their arrival before commencing a two-year indentured labour contract. Memorialisation of these camps tends to present them as the founding places of the migrant experience in Australia; however, there has been very little historical work on displaced persons in Queensland, or on the Queensland migrant camps — Wacol, Enoggera, Stuart and Cairns. This article focuses on recent commemorative attempts surrounding the Stuart migrant camp in order to argue that, in relation to displaced persons, family and community memories drive commemorative activities.